A Review on Antihyperglycemic and Antihepatoprotective Activity of Eco-Friendly Punica granatum Peel Waste. (25th June 2013) - Middha, Sushil Kumar; Usha, Talambedu; Pande, Veena
Abstract : Over the past decade, pomegranate ( Punica granatum ) is entitled as a wonder fruit because of its voluminous pharmacological properties. In 1830, P. granatum fruit was first recognized in United States Pharmacopeia; the Philadelphia edition introduced the rind of the fruit, the New York edition the bark of the root and further 1890 edition the stem bark was introduced. There are significant efforts and progress made in establishing the pharmacological mechanisms of peel (pericarp or rind) and the individual constituents responsible for them. This review provides an insight on the phytochemical components that contribute too antihyperglycemic, hepatoprotective, antihyperlipidemic effect, and numerous other effects of wonderful, economic, and eco-friendly pomegranate peel extract (PP).